Synoptic and local circulations associated with events of high particulate pollution in Valparaiso, Chile. (January 2019) - Pozo, Diana; Marín, Julio C.; Raga, Graciela B.; Arévalo, Jorge; Baumgardner, Darrel; Córdova, Ana M.; Mora, Jorge
Abstract: This study discusses the synoptic situations associated with cases of high pollution in terms of black carbon (BC) concentrations observed at the research site during the four months of the VAMPIRE campaign that is described fully in the companion study by Marín et al. (2017). Cases in which the concentration of BC exceeded the 85 th percentile were selected to evaluate composite synoptic situations, resulting in a total of fifteen cases analyzed. These fifteen cases occurred during one of the three prevalent synoptic situations identified and labeled as: i) Coastal low, characterized by weak easterly winds and low planetary boundary layer (PBL) height due to an enhancement of the temperature inversion before the arrival of the coastal low; ii) Pre-frontal, also characterized by low PBL height, with a cold front approaching from the South and the coastal low retreating northwards, also associated with pollution episodes in Santiago (Rutllant and Garreaud, 1995); and iii) SEP anticyclone characterized by large stability, very low gradient in the mean sea level pressure and weak westerly-southwesterly wind due to the dominance of the southeast Pacific anticyclone. Coastal low cases were observed not only during winter but also in all four months of the VAMPIRE field campaign, while Pre-frontal cases were observed only at the end of July and August 2014. All three synoptic situations are consistent with a reduced synoptic forcing, in which the mesoscale sea-land breeze predominates and advects large pollutant concentrations from local/regional emission sources to the research site. Detailed analysis is presented here for two case studies: one Coastal low and one Pre-frontal, combining the observations of pollutants as well as mesoscale modeling with the WRF model to estimate back-trajectories and evaluate the relative role of the synoptic and mesoscale forcing on the pollution episodes in Valparaiso. These synoptic conditions and their interplay with meso-scale circulations identified during VAMPIRE provide evidence and insight that will aid in future air quality forecasts for Valparaiso.